Pengembangan Media Pembelajaran Berbasis Website "Bang Rugee" Terintegrasi GeoGebra untuk Meningkatkan Pemahaman Bangun Ruang Siswa SMP - Nanda Nacaska Oktihsani Mohammad; Aprilia Dwi Handayani; Ika Santia (Jurnal Ragam Pengabdian, 2026)
This study aimed to develop a website-based learning medium called Bang Rugee (Bangun Ruang GeoGebra Eksploratif Education), which integrates GeoGebra 3D simulations, a solid geometry calculator, and interactive quizzes to enhance Grade VIII junior high school students' understanding of three-dimensional geometry. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The trial involved 34 eighth-grade students at SMP Negeri 1 Ngadiluwih using a one-group pretest-posttest design. Data were collected through expert validation sheets, student and teacher response questionnaires, and multiple-choice achievement tests. The validation results reached an average score of 87.1%, indicating that the medium was highly feasible. Practicality testing showed positive responses from students (93.1%) and teachers (90.6%), classifying the medium as very practical. Effectiveness testing revealed a significant improvement in students’ learning outcomes, with paired sample t-test results showing p < 0.05. The average N-Gain score was 0.42, categorized as moderate, accompanied by a large effect size and an increase in classical learning mastery from 32% to 76%. Furthermore, all students demonstrated improved posttest scores. The study concludes that Bang Rugee is a valid, practical, and effective learning medium for improving students’ understanding of solid geometry concepts and recommends extending similar technology-based media to other mathematics topics.